2009
DOI: 10.1007/s00277-009-0807-6
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of clinically apparent thromboembolism in Korean patients with multiple myeloma treated with thalidomide

Abstract: The frequency of thromboembolic events (TE) in Caucasian patients with multiple myeloma (MM) receiving thalidomide as the initial treatment has been reported to be 10~58% without prophylactic anticoagulation. Korean MM patients treated with thalidomide were studied to determine the frequency of TE and associated risk factors. A retrospective medical record review of the Korean MM registry from 25 centers in Korea between 2003 and 2007 was performed. We assessed the incidence of arterial and venous TE and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
10
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 32 publications
5
10
2
Order By: Relevance
“…The 9Á2% incidence of ATE in our Chinese cohort is higher than the previously reported incidence of 5Á2% in newly diagnosed non-Chinese MM patients and compared to historical data in the Asians (Libourel et al, 2010). While the rate of thromboprophylaxis in our study was lower than in the Korean study, it was higher than in the Taiwanese study suggesting that this may not be the only factor (Koh et al, 2010;Wu et al, 2012). Overall, the Chinese had a significantly lower incidence of arterial risk factors.…”
contrasting
confidence: 76%
See 1 more Smart Citation
“…The 9Á2% incidence of ATE in our Chinese cohort is higher than the previously reported incidence of 5Á2% in newly diagnosed non-Chinese MM patients and compared to historical data in the Asians (Libourel et al, 2010). While the rate of thromboprophylaxis in our study was lower than in the Korean study, it was higher than in the Taiwanese study suggesting that this may not be the only factor (Koh et al, 2010;Wu et al, 2012). Overall, the Chinese had a significantly lower incidence of arterial risk factors.…”
contrasting
confidence: 76%
“…A lower incidence of thrombosis has been noted in Asians with multiple myeloma (MM), although direct comparisons to other races are lacking (Koh et al, 2010;Kristinsson et al, 2010;Carrier et al, 2011). Thromboprophylaxis is not routinely administered to MM patients when treated with immunomodulators in many Asian centres (Musallam et al, 2009;Palumbo et al, 2011;Liew et al, 2012;Wu et al, 2012).…”
mentioning
confidence: 99%
“…The risk is generally greatest in patients treated with thalidomide as a first-line therapy, as opposed to patients treated after relapse [18]. The percentage of thromboembolic events with thalidomide therapy in our study (10%) was higher than previously reported in Korean patients in general (3.9%) [19]. However, this incidence was lower than data from Western cohorts, which showed 6-17% incidences of VTE [5,6,8] after MPT treatment.…”
Section: Discussioncontrasting
confidence: 47%
“…It is noteworthy that the incidence of venous thromboembolism in Asian MM patients on thalidomide and lenalidomide may be less than that of their western counterparts. (38,39) These recommendations should, therefore, be considered in this context, and the risk and benefi t of anticoagulation assessed on a caseby-case basis.…”
Section: Thrombotic Complicationsmentioning
confidence: 99%